Pre School of Children’s Enhancement Certifications through Constructive Beam Game - Mayasari, Ema; Wahyuni, Candra (Universitas STRADA Indonesia, 2018)
Problems on the stimulation provided when the child is a child too are required to develop their cognitive intelligence but limited his creativity. One of the efforts to improve children's creativity is through constructive play. The purpose of this study was to determine the relationship of constructive game block of flats with the development of creativity in pre-school age children in kindergarten Dharma Wanita Tosaren II Kediri. This study was an observational study with cross sectional approach. By using simple random sampling technique obtained a sample 34 respondents. The independent variables studied were constructive play a block of flats, the dependent variable under study was the development of creativity. The instrument used is the observation sheet, the results were analyzed using chi square test at the significant level of 5%. The results showed most respondents carry out constructive play, with 21 respondents (58.33%) and the majority of respondents have a level of creativity in the creative category, ie 19 respondents (52.78%). Results of analysis of the data shows the p-value (0.008) <Î± (0.05), meaning there is a constructive game block of flats with the development of creativity in pre-school age children in kindergarten Dharma Wanita Tosaren II of Kediri with the level of closeness of the relationship in the medium category. Stacking blocks constructive play stimulates the formation of new nerve fibers to improve intelligence and memory of children, in addition to the child's imagination took honed thereby encouraging better kretifitasnya that is able to create something new with a variety that has been exemplified